Enhanced host–guest interaction between [10]cycloparaphenylene ([10]CPP) and [5]CPP by cationic charges - Kayahara, Eiichi; Mizuhata, Yoshiyuki; Yamago, Shigeru (Beilstein Journal of Organic Chemistry, 2024)
A dication of [5]cycloparaphenylene ([5]CPP2+) was selectively encapsulated by neutral [10]CPP to form the shortest double-layer carbon nanotube, [10]CPP⊃[5]CPP2+. While the same host–guest complex consisted of neutral CPPs, [10]CPP⊃[5]CPP, was already reported, the cationic complex showed an about 20 times higher association constant in (CDCl2)2 at 25 °C (103 mol L−1). Electrochemical and photophysical analyses and theoretical calculations suggested the partial electron transfer from [10]CPP to [5]CPP2+ in the complex, and this charge-transfer (CT) interaction is most likely the origin of the higher association constant of the dicationic complex than the neutral one.
Keywords: charge-transfer; cycloparaphenylene; dication; host–guest chemistry